AGRARIAN REFORM AT SIGI REGENCY OF CENTRAL SULAWESI: BETWEEN HOPE AND REALITY - Ismeti (Warmadewa Press, 2021)
The determination of conservation areas without providing a solution overcoming the poverty of society has led to conflict between society and the state. Therefore, Sigi Regency Government-run programs Agrarian Reform in 2016 to reduce poverty and the rare arable land of the community in the area. This study aims to examine the implementation of Agrarian Reform in Sigi, in the perspective of law and human rights. This study applied a qualitative descriptive method by conducting interviews with informants from various sources. The results of this study indicated that there are discrepancies between the regulations and the implementation of agrarian reform in this area, considering the Perpu Number 56, 1960 about the determination of the vast farmland and Government Regulation Number 224, 1961 on the implementation of distribution of land and reparation, as implementing regulations and Presidential Decree Number 86, 2018 of Agrarian Reform. According to the rules of agrarian reform was the distribution of land to the community, as well as eliminating the inequality of land ownership and not solely land certificates. The priority of the recipient of the land was a community that has a land area of less than 0.5 hectares and extensive land in government given aim was an area of 2 hectares. The facts found in Sigi Regency were a free certification for people who already have the land instead of the distribution of land to the people in accordance with the Agrarian Reform, so the programs were conducted in Sigi was not the Agrarian Reform.